Noncoding transcription influences the replication initiation program through chromatin regulation - Soudet, Julien; Gill, Jatinder Kaur; Stutz, Françoise (Genome Research, 2018)
In eukaryotic organisms, replication initiation follows a temporal program. Among the parameters that regulate this program in Saccharomyces cerevisiae, chromatin structure has been at the center of attention without considering the contribution of transcription. Here, we revisit the replication initiation program in the light of widespread genomic noncoding transcription. We find that noncoding RNA transcription termination in the vicinity of autonomously replicating sequences (ARSs) shields replication initiation from transcriptional readthrough. Consistently, high natural nascent transcription correlates with low ARS efficiency and late replication timing. High readthrough transcription is also linked to increased nucleosome occupancy and high levels of H3K36me3. Moreover, forcing ARS readthrough transcription promotes these chromatin features. Finally, replication initiation defects induced by increased transcriptional readthrough are partially rescued in the absence of H3K36 methylation. Altogether, these observations indicate that natural noncoding transcription into ARSs influences replication initiation through chromatin regulation.
10.1101/gr.239582.118